Correlation between the salivary Streptococcus mutans levels and dental caries experience in adult population of Chandigarh, India - Pannu, Parampreet; Gambhir, Ramandeep; Sujlana, Amrita (European Journal of Dentistry, 2013)
Objective: To determine the level of Streptococcus mutans (S. mutans) in adults of Chandigarh and to correlate the dental caries in these individuals with their S. mutans titers. Materials and Methods: Salivary levels of Streptococcus mutans, using Dentocult SM commercial kits were estimated in 200, 25-35 year old adults (males and females). Streptococcus mutans were detected in 87% of the study sample. Score 2, representing 105 - 106 CFU/ml (Colony Forming Unit) of saliva was found to be most prevalent, i.e. in 80 of 200 adults, followed by score 1, depicting S mutans with <105 CFU/ml, in 56 of 200 adults and score 3, with bacterial titer <106 CFU/ml in 38 of 200 adults. Results: Dental caries, recorded using Møller′s index, was found to be maximum in individuals with score 3, followed by score 2,1 and 0, thereby showing a positive correlation of dental caries with increasing titers of S. mutans. This correlation was statistically highly significant in males with figures as 8.73 decayed surfaces at score 2 rising to 17.38 at score 3. The mean of DMFT was higher among females than in the males in the present study. Conclusion: The split up data in males and females, showed a positive association between caries experience and salivary S. mutans scores. The results of the study will serve as a baseline data for future planning of preventive programs in adults.
Keywords: Adults; dental caries; dentocult SM kits; Streptococcus mutans